What It Means for a Concurrent Program to Satisfy a Specification: Why No One Has Specified Priority - Lamport, Leslie (Proceedings of the Twelfth ACM Symposium on Principles of Programming Languages, ACM SIGACT-SIGPLAN, 1985)
I must have spent a lot of time at SRI arguing with Schwartz and Melliar-Smith about the relative merits of temporal logic and transition axioms. (See the discussion of [50].) I don't remember exactly what happened, but this paper's acknowledgment section says that "they kept poking holes in my attempts to specify FCFS [first-come, first-served] until we all finally recognized the fundamental problem [that it can't be done]."